Post-cracking punching shear behavior of concrete flat slabs partially reinforced with full-depth UHPC: Experiment and mechanical model. (15th January 2023) - Zhou, Kai; Qi, Jianan; Wang, Jingquan
Highlights: A mechanical model considering both fibers' contribution and the influence of different UHPC dimensions was firstly proposed. Two new ductility indexes were proposed to evaluate the post-cracking deformability of NC-UHPC composite slabs. The influence of different UHPC dimensions on the post-cracking punching shear behavior was analyzed. The optimal application of UHPC was the area enclosed by a perimeter at 1–2 times of slab thickness from the loading plate. The failure mode changed from brittle punching shear failure to combined punching-flexural failure with the application of UHPC. Abstract: Concrete flat slab partially reinforced with full depth UHPC within the critical punching shear area was considered an advanced and economical form of slabs since the application of UHPC can significantly enhance the punching shear behavior after cracking due to its superior mechanical properties. An experimental study of six flat slabs was conducted to research the post-cracking punching shear behavior of NC-UHPC composite slabs, where the crack pattern, stiffness degradation, post-cracking deformability, and peak strengths under different UHPC dimensions were investigated. The test results revealed that the failure mode of slabs changed from brittle punching failure to ductile combined punching shear-flexural failure when the width of the UHPC coverage area reaches more than 1 times the slab thickness from the periphery of the loading plate face. Two new ductility indexes were proposed to evaluate the post-cracking deformability of NC-UHPC composite slabs, which was improved by about 65 % and 108 %, compared to that of NC slabs, respectively. The influence of different UHPC dimensions on the post-cracking punching shear behavior was analyzed. The optimal application of UHPC in NC-UHPC composite slabs was deemed to be the area enclosed by a perimeter located at about 1–2 times of slab thickness from the periphery of the loading plate face. Meanwhile, the peak strengths of NC-UHPC composite slabs were predicted by two mechanical models. It was concluded that the mechanical model proposed in this paper which consider both fibers' contribution and the influence of different UHPC dimensions can predict the peak strength of NC-UHPC composite slabs accurately.